African farmers and the world market - Giri, Jacques (Technical Centre for Agricultural and Rural Cooperation, 1990)
Jacques Giri Is the author of L'Afrique en panne (Africa at breaking point) and Le Sahel au XXIème siècle (the Sahel in the 21st century) and the founder of SEED - a development strategies consultancy - and is also consultant to the Club du Sahel....